2017
DOI: 10.18182/tjf.328494
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of oriental spruce (Picea orientalis) and oak (Quercus spp.) barks

Abstract: Chemical composition of oriental spruce (Picea orientalis) and oak (Quercus spp.) barksAbstract: In this study, the chemical composition of bark from oriental spruce (Picea orientalis), which occur as a result of logging production of forestry enterprises, and oak (Qercus spp.) bark, which are industrial waste of the wood panel industry after board production, were analyzed by wet chemical analysis of wood and analysis methods of phenolic compound. Ash content values of the barks obtained from Artvin and Trabz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
2
1
4
Order By: Relevance
“…This percentage is close to the percentages found in previous literature studies, which reported 18.8% and 20.07%, reported by Miranda et al (2012) and Fengel and Wegener (1989), respectively. The oak bark extractive content was found to be 18.8%, which was higher than the 11.4% reported by Gönültaş and Uçar (2017). The fir bark extractive content was also 11.4%.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…This percentage is close to the percentages found in previous literature studies, which reported 18.8% and 20.07%, reported by Miranda et al (2012) and Fengel and Wegener (1989), respectively. The oak bark extractive content was found to be 18.8%, which was higher than the 11.4% reported by Gönültaş and Uçar (2017). The fir bark extractive content was also 11.4%.…”
Section: Resultscontrasting
confidence: 67%
“…There have been many topics of bark utilization research. However, bark research can be divided into two main objectives: utilization of their main components (cellulose, lignin, and hemicellulose) (Fengel and Wegener 1989;Usta 1993;Balaban and Ucar 2001;Odabaş-Serin and Gümüşkaya 2006;Safdari et al 2011;Miranda et al 2012;Akgül et al 2013;Serin and Güleç 2014;Durmaz et al 2016;Gönültaş and Uçar 2017), and their secondary metabolite qualities (Sjödin et al 1996;Kuliev et al 1997;Vrkočová et al 2000;Diouf et al 2009;Yesil-Celiktas et al 2009;Duda-Chodak et al 2011;Lee et al 2011;Maimoona et al 2011;Sati et al 2012;Legault et al 2013;Bouras et al 2015;Devappa et al 2015;Hofmann et al 2015;Özgenç et al 2016;Özgenç et al 2017;Dróżdż and Pyrzynska 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Elde edilen sonuçlar incelendiğinde eter fazı 15.02 ve su fazı 27.77 değerleri doğu ladini ve meşe için belirlenen değerlere benzerdir. Fıstık çamı kabuk taneninin incelendiği çalışmada 6.87 ve 36.22 (Gönültaş & Uçar, 2012b), ökaliptus kabuk taneninde 14.39 ve kestane dış kabuğu taneninde 52.17 (Vazquez ve ark., 2009) değerleri belirlenmiştir. Toros sediri tanen ekstraktı örneklerinde bütanol-HCl yöntemine göre antosiyanidin (flavonoid) miktarı 7.61 mg/g CE olarak belirlenmiştir.…”
Section: Bulgular Ve Tartışmaunclassified
“…3282 cm -1 piki fenolik yapıya farklı şekilde bağlı OH gruplarını göstermektedir (Gönültaş & Uçar, 2012a); Gönültaş & Uçar, 2012b;Ricci ve ark., 2015;Ghitescu ve ark., 2015). 3100-2800 cm -1 bölgesi aromatik bileşiklerdeki C-H gerilim bölgesi olarak tanımlanmaktadır.…”
Section: Bulgular Ve Tartışmaunclassified
See 1 more Smart Citation